Effect of Hexagonal Boron Nitride Nanoparticles Additions on Corrosion Resistance for Zinc Coatings of Weathering Steel in Rainwater - Mohsin, Dhurgham A.; Lieth, Haider M.; Jabbar, Murtadha A. (Basrah Journal for Engineering Sciences, 2023)
Zinc and its alloy coatings are commonly used to provide cathodic protection for weathering steel. However, the steel substrate corrodes faster than the Zinc coating because of the coating's negative corrosion potential. Many studies have examined Zinc and alloy coatings' resistance to corrosion. Hot-dip galvanizing, Electrodeposition, and Zinc-rich coat (ZRC) spray are just some of the methods that can be used to deposit such coatings. Commercially available 99.95 % pure Zinc oxide was used in the electroplating process in this investigation. Steel samples were plated in Zinc sulphate and Zinc oxide solutions and were controlled by different bath parameters such as voltage, current, pH, temperature, and coating time. The addition of hexagonal Boron Nitride (h-BN) nanoparticles has also shown significant improvements in corrosion resistance. However, Zinc-based coating techniques reinforced with h-BN incorporation show the best corrosion current density ( I corr ) of Hot dip 2 % wt. (2.1 µA/cm 2 ), ZRC 2.5 % wt., (4.4 µA/cm 2 ), and electroplating 15.75 g/L (0.081 µA/cm 2 ), which is an order of magnitude lower than coatings without h-BNs. The corrosion rates and current densities of Zn/h-BN coated layers were investigated in a controlled laboratory environment that mimicked natural conditions (Rainwater solution) by extrapolating polarization curves.